KAJIAN TERHADAP CARA EVALUASI STATUS KESUBURAN TANAH DAN PEMANFAATANNYA SEBAGAI DASAR PENGELOLAAN HARA SPESIFIK LOKASI PADI SAWAH IRIGASI DI KABUPATEN BURU - , ANDRIKO NOTO SUSANTO, SP., MP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Fertilization recommendation based on precision mapping of paddy soil fertility status can improve the fertilization efficiency, optimize the productivity of rice, and minimize the risk of environmental degradation. Study with the aim of testing the accuracy of some methods of evaluating soil fertility status (SFS) as the basis in determining site-specific nutrient management of N, P and K paddy soil recommendation have been conducted on irrigated paddy soil in Waeapo plain, Buru. Five methods were tested including FAOâs method (1983), PPTâs method (1983) and three of Kyumaâs methods (2004), namely the status of Inherent potentiality (IP), organic matter and N status (OM), and available phosphate status (AP). Fertilizer recommendation was determined by omission plot trials based on SFS selected map. The results showed that the IP-method of Kyuma (2004) had the highest positive correlation with rice productivity compared to the FAO and the PPT methods. The land area of very low status of IP-Kyuma was 18,813.76 ha (72.78%) and the low was 7,035.07 ha (27.22%). The average of paddy fieldâs fertilizer addition in very low SFS was 120.20 kg N/ha, 13.03 kg P/ha, and 58.12 kg K/ha with grain yield target of 8 ton/ha, while in low SFS was 136.53 kg N/ha, 13.46 kg P/ha and 58.97 kg K/ha with 8.3 ton/ha grain yield target. The area fertilizer recommendation with very low SFS is divided into two, they are SR-I, covering an area of 14,830.02 ha (57.37%) and SR-II covering an area of 4,722.42 ha (18.27%), while the low SFS can be divided into three namely R-I with area of 3,763.67 ha (14.56%), R-II with area of 1,022.11 ha (3.95%), and R-III with area of 1,510.60 ha (5.84%). The application of site-specific fertilizer recommendation increased the productivity from 5.43 ton/ha (farmer practices) to 6.53 ton/ha